Perceived and posttraumatic stress is associated with decreased learning, memory, and fluency in HIV-infected women. (13th November 2017) - Rubin, Leah H.; Cook, Judith A.; Springer, Gayle; Weber, Kathleen M.; Cohen, Mardge H.; Martin, Eileen M.; Valcour, Victor G.; Benning, Lorie; Alden, Christine; Milam, Joel; Anastos, Kathryn; Young, Mary A.; et al.
Abstract : Objective: Psychological risk factors (PRFs) are associated with impaired learning and memory in HIV-infected (HIV+) women. We determined the dynamic nature of the effects of PRFs and HIV serostatus on learning and memory over time. Design: Multicenter, prospective cohort study. Methods: Every 2 years between 2009 and 2013 (three times), 646 HIV+ and 300 demographically similar HIV-uninfected (HIV−) women from the Women's Interagency HIV Study completed neuropsychological testing and questionnaires measuring PRFs [perceived stress, posttraumatic stress disorder (PTSD) symptoms, depressive symptoms]. Using mixed-effects regressions, we examined separate and interactive associations between HIV-serostatus and PRFs on performance over time. Results: HIV+ and HIV− women had similar rates of PRFs. Fluency was the only domain in which performance over time depended on the combined influence of HIV-serostatus and stress or PTSD ( P  < 0.05), not depression. In HIV, higher stress and PTSD were associated with a greater cognitive decline in performance ( P  < 0.05) vs. lower stress and PTSD. Irrespective of time, performance on learning and memory depended on the combined influence of HIV-serostatus and stress or PTSD ( P  ⩽ 0.05). In the context of HIV, stress and PTSD were negatively associated with performance. Effects were pronounced on learning among HIV+ women without effective treatment or viral suppression. Regardless of time or HIV-serostatus, all PRFs were associated with lower speed, global neuropsychological, and executive function. Conclusion: More than depression, perceived stress and PTSD symptoms are treatment targets to potentially improve fluency, learning, and memory in women living with HIV particularly when HIV treatment is not optimal. Abstract : Supplemental Digital Content is available in the text